Income Distribution of People of Retirement Age in Japan - Yamada, Atsuhiro (Journal of Income Distribution®, 2007)
This article examines inequality and poverty among older peoplein Japan. It compares Japan with that of a sample of other OECD countries.Provisions within the social insurance system that enable old-agepensioners to work and draw incomes from labor explain some of theinequality and poverty that is seen in Japan. So, too, do the low rate oftake up of social assistance, the low level of benefits available from thefirst tier pension, the uneven coverage of second-tier pensions, the lackof progressiveness of the income tax system and the fact older peoplelive in multi-generational households whilst others live alone.